Cybernook inauguration - Library, De La Salle University, Manila (Animo Repository, 1996)
De La Salle University launched the cybernook, a small cozy area in the University library where students can surf the net. Dr. Linda Posadas, Executive Director of the Department of Science and Technology-Philippine Council for Advanced Science and Technology (DOST-PCAST) gave the talk on IT Development in Education.